From Pork-Barrel Machine to Relevant Policy Communication Platform? Transition of LDP’s Personal Support Group Koenkai in the Japanese Political System - Popiołek, Zachariasz (Rethinking Asia in World Politics, 2023)
Koenkai 後援会 individual support group of Japanese politicians has become phenomenon that has no equivalent in any Western democratic country. It emerged on political scene long before introduction of universal suffrage, have spread in the post-war period of rapid democratization due to electoral campaign constraints, and survived until today despite of major evolutions of political environment. The aim of this paper is to show the historical trajectory of individual support groups development and attempt to answer the question if Koenkai’s funds distribution function-claimed in previous research remains valid. To prove the above I have examined previous research, utilized data of public opinion pools executed by Akarui Suishin Kyokai (Clean Election League) and financial reports submitted by support groups to electoral commissions in each of 47 prefectures and Ministry of Internal Affairs and Communications.